2010
DOI: 10.1186/1742-4690-7-51
|View full text |Cite|
|
Sign up to set email alerts
|

HIV-1 Vpu and HIV-2 Env counteract BST-2/tetherin by sequestration in a perinuclear compartment

Abstract: BackgroundIn the absence of the Vpu protein, newly formed HIV-1 particles can remain attached to the surface of human cells due to the action of an interferon-inducible cellular restriction factor, BST-2/tetherin. Tetherin also restricts the release of other enveloped viral particles and is counteracted by a several viral anti-tetherin factors including the HIV-2 Env, SIV Nef and KSHV K5 proteins.ResultsWe observed that a fraction of tetherin is located at the surface of restricting cells, and that co-expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
164
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(174 citation statements)
references
References 48 publications
(103 reference statements)
10
164
0
Order By: Relevance
“…This Env‐mediated neutralization of BST‐2 effect is similarly to the antagonistic actions of Vpu 93, 94 and as reported earlier for Vpu in promoting viral particle release 95, 96, 97, 98, 99. Env interacts with BST‐2 but the domains involved in the interaction are yet to be identified.…”
Section: Viral Glycoproteins and Bst‐2 Neutralizationsupporting
confidence: 77%
“…This Env‐mediated neutralization of BST‐2 effect is similarly to the antagonistic actions of Vpu 93, 94 and as reported earlier for Vpu in promoting viral particle release 95, 96, 97, 98, 99. Env interacts with BST‐2 but the domains involved in the interaction are yet to be identified.…”
Section: Viral Glycoproteins and Bst‐2 Neutralizationsupporting
confidence: 77%
“…Indeed, prior to the identification of tetherin, the envelope glycoproteins of certain HIV-2 isolates were shown to have "Vpu-like" activity that could rescue the release of Vpu-deficient HIV-1 from restrictive cells (62). Tetherin antagonism by Env depends on physical interaction between Env and tetherin and on a conserved tyrosine-based endocytosis motif (YXX) in the cytoplasmic tail of the Env transmembrane protein gp41 (59,60,63). The residues that contribute to Env-tetherin interactions are not well defined but appear to be located in the extracellular domains of both proteins based on analyses of recombinant forms of Env and tetherin (60,64) and on the identification of defined amino acid changes in the ectodomains of gp41 and tetherin that disrupt anti-tetherin activity (64 -66).…”
Section: Restriction By Particle Tethering: Bst-2/tetherin Integral Mmentioning
confidence: 99%
“…The residues that contribute to Env-tetherin interactions are not well defined but appear to be located in the extracellular domains of both proteins based on analyses of recombinant forms of Env and tetherin (60,64) and on the identification of defined amino acid changes in the ectodomains of gp41 and tetherin that disrupt anti-tetherin activity (64 -66). Interaction with Env does not result in the degradation of tetherin but instead leads to internalization and sequestration of tetherin away from sites of virus release at the plasma membrane by a clathrin-dependent pathway (57,60,63).…”
Section: Restriction By Particle Tethering: Bst-2/tetherin Integral Mmentioning
confidence: 99%
“…However, some of these viruses possess their own antagonizing BST2 counterparts instead of Vpu. For instance, HIV-2 counteracts BST2 with its envelope glycoprotein (Env) (8,13,15,30), while SIVsmm/mac impairs the tethering function of simian BST2 with its accessory protein, Nef (15,58,73). In addition, it was reported that Ebola virus glycoprotein (24) and the K5 protein of Kaposi's sarcoma-associated herpesvirus (34,46) can counteract BST2.…”
Section: Wt]) Hiv-1-infected/transfected Cells In Certain Cd4mentioning
confidence: 99%